Exchange transfusion in neonates: An experience from a tertiary care center in North India - Naranje, Kirti M; Singh, Anita; Panghal, Astha; Pandita, Aakash; Gupta, Girish (Indian Journal of Child Health, 2019)
Background: Blood exchange transfusion (ET) involves replacement of affected neonate’s blood with compatible donor blood. Although the use of ET has decreased over years, it still remains a popular emergency rescue procedure for newborns with severe jaundice. Objective: The study was done to describe the indications and complications associated with ET in a 20 bedded neonatal unit of a tertiary care center in North India. Materials and Methods: This was a retrospective observational cohort study of neonates who underwent ET from July 2014 to May 2019. Demographic profile, indications and etiology, details of ET procedure, and related adverse events were noted from medical records and chart review. Results: Of 2310 admitted neonates, 77 (3.3%) underwent 103 ETs during the study period with an average rate of 23.3 ETs per year. Hyperbilirubinemia was the most common indication for ET in 53 (68.8%) neonates. Rhesus (Rh) hemolytic disease was the single most frequent etiology for hyperbilirubinemia seen in 43 (55.8%) neonates. A total of 77 adverse events related to ET were seen in 53 (68.8%) neonates whereas 17 (22%) had more than one adverse event. The most common complication was thrombocytopenia in 40 (51.9%) neonates. Overall, mortality was 7 (9.1%); none were attributable to ET. Conclusion: The study identifies Rh hemolytic disease of newborn as the most common etiology leading to ET in newborns. Although ET is a relatively safe procedure, the high incidence of adverse events suggests vigilant monitoring and in-depth expertise for performing and managing complications of the procedure.